Inclusive Opportunities: Vocational Training and Employment for Women with Disabilities in My Tho City, Tien Giang Province - Nguyen Nu Nguyet Anh; Nguyen Thi Phuong Uyen (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
In Vietnam, the number of persons with disabilities constitutes a significant proportion of the total population. The unemployment rate among women with disabilities is particularly high. Access to employment for women with disabilities is a social problem that needs to be addressed due to its long-term effects on individuals, their families, and their communities. This paper describes the characteristics of women with disabilities in My Tho City, Tien Giang Province before examining vocational training programs designed for individuals with disabilities and explores the pathways through which women with disabilities in this locality can access employment. In addition to secondary sources, this study collected primary data in 2022 through 33 semi-structured in-depth interviews with women with disabilities, representatives of local government from Ward 5, Ward 6, Dao Thanh and My Phong, a representative of the Women’s Union, and a representative of Department of Labor, Invalid, and Social Affairs from within the city. Based on the research results, the paper offers several recommendations to enhance employment opportunities for this group, contributing to the United Nations Sustainable Development Goals. Received 25th July 2024; Revised 25th August 2024; Accepted 7th October 2024